Study on the Development of Test Equipment of Slat Sector Gear Transmission Mechanism - Hao Hongwu; Duan Yajun (Jixie chuandong)
In order to verify the components strength of slat sector gear transmission mechanism,moreover improve its service life,transmission stability and transmission accuracy,the loading and control method of slat sector gear transmission mechanism testing is analyzed according to the development and production demand of a certain type aircraft slat sector gear transmission mechanism. The test equipment of slat sector gear transmission mechanism is developed by using the principle of motion similarity and dynamic similarity,and the equipment adopted closed loop control and hydraulic loading. The static strength test and delivery running-in of the slat sector gear transmission mechanism are carried out by this equipment,and the results of these works are good.The requirements of running-in and relevant test is satisfied.